Hubungan Antara Rata-Rata Pendapatan Keluarga dan Tingkat Kedewasaan Ibu Dengan Tingkat Pengetahuan Ibu Tentang Diare pada Balita di Wilayah Kerja Puskesmas Cisadea Kecamatan Blimbing Kota Malang - Puspita Indahsari, Shyska Yuli; Budiwanto, Setyo; Katmawanti, Septa (Preventia: The Indonesian Journal of Public Health, 2020)
An increase in diarrhea suffers on toddler in the working area primary health centre cisadea at last three years did not escape the knowledge factor in the care of a mother, here a mother’s maturity and family income can encourage a degree of family healthespecially under five children. The purpose of this research is to know the relation of mother’s age group and average income of family ith a mother’s level knowledge about diarrhea in under five children. Research methods used is rasearch correlational. The subject in this study as many as 20 mothers of child under five who are never treated in primary health care Cisadea ith complain of diarrhea. The instrument used in the form of a knowledge test, questionnaire and the documentation. Data analysis using chi-square tes. The results showed that: (1) chi-square Value (X2Count) mother’s maturity level82.002 more than value X2Table 11.070, (2) chi-square Value (X2Count) average income of family 40.992 more than X2Table 7.815, (3) chi-square Value (X2Count) mother’s maturity level and average income of family with mother’s level knowledge about diarrhea in under five children 122.994 more than X2value Table 21.026. Conclusion: (1) There is a significant correlation between the mother’s maturity levelwith mother’s level knowledge about diarrhea in under five children, (2) There is a significant correlation between average income of family with mother’s level knowledge about diarrhea in under five children.